Does Bosentan Protect Diabetic Brain Alterations in Rats? The Role of Endothelin‐1 in the Diabetic Brain. (7th October 2014) - Demir, Recep; Cadirci, Elif; Akpinar, Erol; Cayir, Yasemin; Atmaca, Hasan Tarik; Un, Harun; Kunak, Celalettin Semih; Yayla, Muhammed; Bayraktutan, Zafer; Demir, Ilknur
Abstract Diabetes mellitus (DM) is a major problem all over the world, affecting more people in recent years. Individuals with diabetes are more prone to disease than non‐diabetics, especially vascular complications. The aim of this study was to examine the roles of the endothelin (ET)‐1 in brain damage formed in a streptozocin (STZ)‐induced diabetes model, and the effect of bosentan, which is the non‐specific ET1 receptor blocker in the prevention of the diabetes‐induced brain damage. To examine the effects of bosentan (50 mg/kg and 100 mg/kg) in this study, the rats were given the drug for 3 months. The rats were divided into four groups: the sham group (n = 10), the diabetic control group (n = 10), the group of diabetic rats given bosentan 50 mg/kg (n = 10) and the group of diabetic rats given bosentan 100 mg/kg (n = 10). Diabetes was induced in the rats by STZ (60 mg/kg i.p.). On day 91, all rats were killed. Brain tissues of the rats were measured by molecular, biochemical and histopathological methods. Antioxidant levels in the therapy groups were observed as quite near to the values in the healthy group. In this study, while the brain eNOS levels in the diabetic groups decreased, the ET1 and iNOS levels were found to be increased. However, in the diabetes group, hippocampus and cerebellum, pericellular oedema and a number of neuronal cytoretraction were increased in neuropiles, whereas these results were decreased in the therapy group. Based on all of these results, ET1 will not be ignored in diabetes‐induced cerebral complications.